Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Minat Investasi Mahasiswa Fakultas Ekonomi Universitas Pendidikan Ganesha - Gumilang, Panji; Irwansyah, M. Rudi (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the effect of financial literacy and lifestyle on the investment interest of students of the Faculty of Economics, Ganesha University of Education. The design of this study is quantitative causal. This study took samples based on probability sampling with stratified sampling techniques. The population in this study was 2689 people who had the status of students of the Faculty of Economics, Ganesha University of Education, and the sample used was 96 people based on the Slovin formula. The data analysis technique used was multiple linear regression analysis with partial (t-test) and simultaneous (f-test) hypothesis testing. The results of this study indicate that (1) financial literacy has a positive effect on the investment interest of students of the Faculty of Economics, Universitas Pendidikan Ganesha; (2) lifestyle has a positive effect on the investment interest of students of the Faculty of Economics, Universitas Pendidikan Ganesha; and (3) financial literacy and lifestyle have a positive effect on the investment interest of students of the Faculty of Economics, Universitas Pendidikan Ganesha.